1998
DOI: 10.1097/00007890-199803270-00007
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Increased Expression of Inducible Nitric Oxide Synthase in Human Allograft Rejection1

Abstract: Apoptosis is a major form of myocyte death during human cardiac allograft rejection. Cardiac myocyte apoptosis is closely associated with expression of iNOS in macrophages and myocytes and with nitration of myocyte proteins by peroxynitrite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 43 publications
0
60
0
1
Order By: Relevance
“…23 Apoptosis of cardiac myocytes and of infiltrating macrophages has also been observed in parallel with the upregulation of iNOS mRNA, protein, and enzyme activity in rejecting rat cardiac allografts and in human endomyocardial biopsies from hearts undergoing class 3 (ISHLT) rejection. 18,48 These associations, along with in vitro studies of NO-mediated cardiomyocyte apoptosis, have suggested that NO may be an apoptotic trigger in this situation. 49,50 The slight reductions observed in apoptotic cell numbers in the animals treated with the COX-2 and iNOS inhibitors were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…23 Apoptosis of cardiac myocytes and of infiltrating macrophages has also been observed in parallel with the upregulation of iNOS mRNA, protein, and enzyme activity in rejecting rat cardiac allografts and in human endomyocardial biopsies from hearts undergoing class 3 (ISHLT) rejection. 18,48 These associations, along with in vitro studies of NO-mediated cardiomyocyte apoptosis, have suggested that NO may be an apoptotic trigger in this situation. 49,50 The slight reductions observed in apoptotic cell numbers in the animals treated with the COX-2 and iNOS inhibitors were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in human cardiac transplantation, evidence of increased apoptosis was more likely to be associated with increased cardiac dysfunction (Birks et al, 2000). Clinically, the importance of peroxynitrite formation was also suggested from previous studies showing increased immunostaining for nitrotyrosine in biopsies of human cardiac grafts with grade III rejection scores but not in biopsies with grade 0 histological rejection scores (Szabolcs et al, 1998). In a recent study, we have shown that neutralizing NO directly limits the extent of protein nitration in rat cardiac transplants and prolongs graft survival (Pieper et al, 2004).…”
mentioning
confidence: 85%
“…Besides above mentioned studies which in part have been performed in human cells it appears that apoptosis, iNOS induction, and human cardiac allograft rejection and/or chronic heart failure are positively correlated. It is assumed that iNOS in macrophages or mycocytes is involved in regulating apoptosis 64,65 in close analogy to iNOS expression and apoptosis in human vascular smooth muscle cells. 44 Furthermore, the appearance of p53 and iNOS in apoptotic macrophages is established in human atherosclerotic lesions.…”
Section: Lessons From Disease Statesmentioning
confidence: 99%